2018
DOI: 10.1002/apj.2270
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and strength‐enhanced nanosilica‐based composite gel for well temporary plugging in high‐temperature reservoirs

Abstract: Polymer gel is widely used for well temporary plugging in petroleum engineering. This paper researched on a novel environmental and strength‐enhanced composite gel plug prepared by the nanosilica, the polymer hydrolyzed polyacrylamide and environmental friendly crosslinker polyethyleneimine, and the effect of strength enhancement and thermal stability mechanism of the nanosilica in this system was investigated. The experiments results showed that with the increase of the nanosilica concentration, the elastic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Chen et al added 1 wt % nano-SiO 2 to the HPAM/PEI gel system, which could form a polymer gel system with higher strength at 130 °C. Jia and Yang found that when the nano-SiO 2 content increased to 8 wt %, high-strength polymer gel could be formed at 130 °C. However, the related gelation mechanism of the above nanoparticle-enhanced HPAM/PEI gels is still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al added 1 wt % nano-SiO 2 to the HPAM/PEI gel system, which could form a polymer gel system with higher strength at 130 °C. Jia and Yang found that when the nano-SiO 2 content increased to 8 wt %, high-strength polymer gel could be formed at 130 °C. However, the related gelation mechanism of the above nanoparticle-enhanced HPAM/PEI gels is still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the high storage modulus values of the PAM/PEI gel, the new wellbore strengthening and water-shutoff application require enhanced strength. Many materials such as silica, clays, and oxides of aluminum, magnesium, and zinc have been implemented to reinforce the composed gel during the cross-linking of polymer solutions. , Silica has capabilities to extend the thermal as well as salinity tolerance of the base fluids after bridging the polymer chains . Moreover, it has a high surface area which is beneficial in providing a more stable structure through increasing the tie points between the polymer entanglement .…”
Section: Introductionmentioning
confidence: 99%
“…Herein, hydrogels are used as profile control and water shutoff agents to adjust the flow direction of the flooding water and drive more crude out to enhance oil recovery . They can also be used as a temporary plugging fluid to prevent the workover fluid in the well bore from leaking into the stratum during the workover process. The hydrogel can be used as an annulus sealant. In the production process of oil and gas wells, after an interlayer cross flow is formed in the annulus by the crack of the annulus cement ring, the hydrogel is squeezed into the channel to prevent the fluid flow from high-pressure formation to low-pressure formation through the channel.…”
Section: Introductionmentioning
confidence: 99%